Penerapan Model Pembelajaran Think Pair Share Untuk Meningkatkan Hasil Belajar IPS Siswa Kelas IV SD Inpres Luaan - Norma N. Monigir (Peneliti.net, 2022)
This research was conducted based on the results of observations made on students of SD Inpres Luaan Tondano, in social studies learning conducted by the teacher is more monotonous, the level of student attention and student activity is still lacking and there is a sense of boredom and disinterest in social studies learning. This is because the teacher only teaches using the lecture method without involving students directly in the learning process so that students' understanding of the material is still relatively low, students are more required to memorize a lot without having to understand the material. Of the 16 students who got high scores only 4 students, while the remaining 12 students got low scores. The purpose of this study was to improve social studies learning outcomes through the application of the Think Pair and Share learning model for fourth grade students of SD Inpres Luaan Tondano. The method used in this research is classroom action research (PTK) from Kemmis and Mc.Taggart (Zainal Aqib, 2006: 31), with four stages, namely: planning, action, observation and reflection in two cycles. Student learning outcomes in cycle I 52.18% and cycle II 92, 18%. In conclusion, the application of Think Pair and Share learning model can improve social studies learning outcomes of fourth grade students of SD Inpres Luaan Tondano. Therefore the author gives advice to the fourth grade teacher so that in the learning process is expected to apply the Think Pair and Share model so that students are more active and motivated to learn.